Evaluation of the Regional Head Age Limit Policy in Indonesia After the Supreme Court Decision Number 23 P / HUM / 2024 - Hamid, La Ode Purnama; Islami, Nabiel Fikril; Jaya, Karman (West Science Law and Human Rights, 2024)
This study evaluates the regional head age limit policy in Indonesia following the Supreme Court Decision Number 23 P/HUM/2024 through a normative juridical analysis. The age limit policy, governed by Law No. 10 of 2016, aims to ensure capable leadership by imposing a minimum age requirement for candidates. However, the Supreme Court's decision raises questions about the policy's alignment with constitutional principles of equality, non-discrimination, and democratic participation. The analysis examines statutory regulations, legal principles, and comparative insights from other democratic countries to understand the policy's rationale and implications. Findings highlight the need for a balanced approach that ensures legal consistency and promotes inclusive, effective regional governance. Recommendations include lowering the minimum age requirement, implementing a flexible age range, and incorporating empirical evidence to refine the policy, ensuring it serves the principles of justice, democratic participation, and effective governance.